44. Przekształć iloczyny na sumy.
a)
[tex]( \sqrt{3} + 1)(2 \sqrt{3} - 2)[/tex]
b)
[tex]( \sqrt{2} + \sqrt{3} )( \sqrt{5} + 1)[/tex]
c)
[tex]( \sqrt{2} + 1)(5 - 2 \sqrt{2} )[/tex]
d)
[tex](2 + \sqrt{2} )(2 \sqrt{2} + 3)[/tex]


Odpowiedź :

Odpowiedź i szczegółowe wyjaśnienie:

[tex]a)\ (\sqrt3+1)(2\sqrt3-2)=\sqrt3\cdot2\sqrt3-2\sqrt3+2\sqrt3-2=2\cdot3-2=4\\\\b)\ (\sqrt2+\sqrt3)(\sqrt5+1)=\sqrt2\cdot\sqrt5+\sqrt2+\sqrt3\cdot\sqrt5+\sqrt3=\\=\sqrt{10}+\sqrt2+\sqrt{15}+\sqrt3\\\\c)\ (\sqrt2+1)(5-2\sqrt2)=5\sqrt2-\sqrt2\cdot2\sqrt2+5-2\sqrt2=\\=5\sqrt2-2\cdot2+5-2\sqrt2=3\sqrt2-4+5=3\sqrt2+1\\\\d)\ (2+\sqrt2)(2\sqrt2+3)=2\cdot2\sqrt2+2\cdot3+\sqrt2\cdot2\sqrt2+3\sqrt2=\\=4\sqrt2+6+2\cdot2+3\sqrt2=7\sqrt2+6+4=7\sqrt2+10\\[/tex]